2014
DOI: 10.1002/hbm.22703
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity mapping of regions associated with self‐ and other‐processing

Abstract: Neuroscience literature increasingly suggests a conceptual self composed of interacting neural regions, rather than independent local activations, yet such claims have yet to be investigated. We, thus, combined task-dependent meta-analytic connectivity modeling (MACM) with task-independent resting-state (RS) connectivity analysis to delineate the neural network of the self, across both states. Given psychological evidence implicating the self’s interdependence on social information, we also delineated the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
80
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 149 publications
(235 reference statements)
13
80
0
2
Order By: Relevance
“…These results match the resting-state functional connectivity when the pACC is treated as a seed [62]. Similarly, clinical work has shown changes of neural coupling between the medial PFC and other brain regions when patients process self-related information [63,64].…”
Section: Self-reference Enhances the Coupling Between Brain Regionssupporting
confidence: 81%
See 1 more Smart Citation
“…These results match the resting-state functional connectivity when the pACC is treated as a seed [62]. Similarly, clinical work has shown changes of neural coupling between the medial PFC and other brain regions when patients process self-related information [63,64].…”
Section: Self-reference Enhances the Coupling Between Brain Regionssupporting
confidence: 81%
“…Indeed, a meta-analysis has demonstrated that there is enhanced neural coupling for selfprocessing (vs other-related processing) between the vmPFC/pregenual anterior cingulate (pACC) and several other regions including the bilateral anterior insula, left striatum, right thalamus, and amygdala [62]. These results match the resting-state functional connectivity when the pACC is treated as a seed [62].…”
Section: Self-reference Enhances the Coupling Between Brain Regionssupporting
confidence: 69%
“…self-relevant traits, own name, own face, autobiographical memories) as opposed to stimuli related to others. Several key regions along the cortical midline appear to show greater activation to self-related stimuli than other-related stimuli (Heatherton, 2006;Northoff et al, 2006;Northoff, Qin, & Feinberg, 2011), including the anterior cingulate cortex (Leshikar, Cassidy, & Gutchess, 2016), the medial prefrontal cortex (mPFC) and the vAI (Murray, Debbané, Fox, Bzdok, & Eickhoff, 2015). The mPFC is particularly involved in the processing of information about people's traits, preferences and beliefs (Frith & Frith, 2003;Ma, Baetens, Vandekerckhove, Van der Cruyssen, & Van Overwalle, 2013;Schilbach, 2015) and shows sensitivity to a number of social factors including social status and ostracism (Muscatell et al, 2012;Powers, Wagner, Norris, & Heatherton, 2013).…”
Section: Conceptual Selfmentioning
confidence: 99%
“…Finally, the self/other dimension refers to the commonality between the developmental and brain systems underpinning the attribution of mental states of the self and of others (Murray et al 2015). Accurate mentalizing inferences are primarily dependent on the relative balance between the systems underpinning each dimension, while biased inferences associated with psychopathology emerge under conditions that lead to a loss of balance (Luyten and Fonagy 2015).…”
Section: Early Hoc Impairments In Chr Youths: Towards An Mbt Approachmentioning
confidence: 99%